(untitled) (Natural Resources and Technology, 2017)
The current and recent activities in the lead-zinc Sasa mine or copper Bucim mine and flotation of galena and sphalerite or chalcopyrite, producing metals for market, are reason for possible troubles from tailing dam-pond and surrounding river, ambient air and plant dust. This appearance is significant for the surrounding environment, but legislative and ecological law directive limited the quantity of these. In this paper will be present results of investigations from plant (flotation), crushing and grinding section, ambient around the mine etc. with quality of ambient air and presence of dust in the environment using appropriate apparatus for these measurements.